Three-tier Test to Identify Students’ Misconception of Human Reproduction System - Wahid Hasyim; Hadi Suwono; Herawati Susilo (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: The purpose of this research was to develop a three-tier test of the human reproductive system in identifying student misconceptions. The instrument was developed by Treagust model which has three stages of defining content; obtain information; development of diagnostic tests. A total of 100 students were subjected. All question items consist of 15 items have been classified as valid, with result of reliability analysis equal to 0.717, average test of power difference 0.45, all item problem is in range 0.35–0.67 at level of difficulty, construct validity r = 0.531, N = 100, p = 0.000. False negative content validity test is 6.47% and false positive is 9.07%. Based on the analysis result, this instrument is feasible to identify student misconception.Key Words: human reproduction system, misconception, three-tier test, studentAbstrak: Tujuan penelitian ini untuk mengembangkan instrumen three-tier test sistem reproduksi manusia dalam mengidentifikasi miskonsepsi siswa. Instrumen dikembangkan dengan model Treagust yang memiliki tiga tahapan yaitu mendefinisikan konten; memperoleh informasi; pengembangan tes diagnostik. Sebanyak 100 siswa dijadikan subjek. Seluruh item soal terdiri 15 butir soal tergolong valid, dengan hasil analisis realibilitas sebesar 0.717, rerata uji daya beda 0.45, semua item soal berada pada rentangan 0.35–0.67 pada tingkat kesukaran, validitas konstruknya r = 0.531, N = 100, p = 0.000. Uji validitas konten persentase false negative sebesar 6.47% dan false positive sebesar 9.07%. Berdasarkan hasil analisis maka instrumen layak untuk mengidentifikasi miskonsepsi siswa.Kata kunci: sistem reproduksi manusia, miskonsepsi, three-tier test, siswa